Oral health status before, during and after antineoplastic treatment at a cancer institute in Barranquilla, Colombia. - Martha Rebolledo-Cobos; Jonathan Harris-Ricardo; Marisol Sánchez-Molina; Justo Pico-Plata; Leidys Calvo-López; Sandra Espitia-Nieto; Andrés Lozano-Gómez (Universidad de Concepción., 2019)
Chemotherapy and radiotherapy are aggressive treatments for cancer management. Both therapies make the stomatogatic system vulnerable to adverse effects on the oral mucosa and hard tissues. This may result in severe oral complications that can affect the quality of life of the oncologic patient. Consequently, oral diagnosis and interdisciplinary management by the stomatologist are critical for cancer treatment, regardless of its location. Objective. To determine the oral health status of cancer patients before, during and after antineoplastic treatment at a cancer institute in the city of Barranquilla, Colombia. Materials and Methods. A descriptive, longitudinal and prospective study of 131 cancer patients, was conducted. The study consisted of initial stomatological assessment of the antineoplastic therapy; classification according to the antineoplastic therapy given by the oncologist; a second stomatological assessment during treatment; and a final stomatological assessment or evaluation forty days after the end of therapy. Descriptive statistics, chi-square and MacNemar test were used to compare and identify variances at the different stages. Results. Female patients accounted for 69%, and breast cancer had 24% prevalence among the included subjects. At the initial stomatological assessment, high frequency lesions were identified, such as generalized biofilm-associated gingivitis in 69% of the cases, followed by oral candidiasis in 61%. The specific prevalence of lesions was 10.65%. In the second stomatological assessment, a greater frequency of periodontal abscesses was observed in 31%, and oral mucositis type II in 18%. The third clinical assessment showed significant changes in oral health status; an increase in the frequency of gingivitis was found in 9.9% (p<0.001); unlike before and during, there was an increment in dental caries of 26.73% (p<0.00000) at this last stage, root remains increased by 39.53% (p<0.00000), and finally, xerostomia increased by 45%. Oral candidiasis was the only lesion that showed improvement. Conclusion. An increase in the number of lesions was observed during and after antineoplastic treatment. The oral cavity is susceptible to antineoplastic treatments; gingivitis, candidiasis, xerostomia, and mucositis were observed, among others conditions.